EFFECT OF CASH FLOW VOLATILITY, GROWTH OPPORTUNITIES, AND DIVIDEND POLICY ON HEDGING DECISIONS: (Empirical Study on Mining Companies Listed on the Indonesia Stock Exchange 2016-2020) - Rahmat Pirmansyah Hasim; Holiawati (Transpublika Publisher, 2022)
This study aims to examine the effect of Cash Flow Volatility, Growth Opportunities, and Dividend Policy on Hedging Decisions. This type of research is quantitative associative. With the population study consist of mining companies listed on the Indonesia Stock Exchange in 2016 – 2020. Meanwhile, the sampling technique used is purposive sampling. Hence, the number of samples obtained in this study as many as 13 companies with data obtained as much as 65 data. The analysis technique used is logistic regression analysis. This research is processed using e-views 10 software. The results revealed that Cash Flow Volatility, Growth Opportunities, and Dividend Policy have a significant effect on Hedging Decisions. Besides, Cash Flow Volatility and Growth Opportunity variables have a significant effect on Hedging Decisions, while Dividend Policy Variables have no effect on Hedging decisions.